1981
DOI: 10.1099/0022-1317-53-2-197
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Subviral Structures from Tomato Spotted Wilt Virus

Abstract: SUMMARYParticles of a stable isolate of tomato spotted wilt virus (TSWV) had a density of 1-147 g/ml in sucrose and contained four major structural proteins of mol. wt.: 1, 26 × 103; 2, 52× 103; 3, 56× 103; and 4, 78× 103 . The RNA which was not infectious consisted of four segments ofmol, wt.: 1, 3.6 x 106; 2, 2.8 × 106; 3, 2.0 × 106; and 4, 1.3 × 106. The ribonucleoprotein (RNP) of TSWV, prepared by treatment of purified virus with Nonidet P-40, could be separated into three components by sedimentation on su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
3

Year Published

1983
1983
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 6 publications
1
21
0
3
Order By: Relevance
“…The virus contains three ssRNA segments, S (2.9 kb), M (5.0 kb) and L (8.9 kb). Each RNA segment is associated with nucleocapsid (N) proteins to form pseudo-circular nucleocapsid structures (van den Hurk et al, 1977;Mohamed, 1981;de Haan et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The virus contains three ssRNA segments, S (2.9 kb), M (5.0 kb) and L (8.9 kb). Each RNA segment is associated with nucleocapsid (N) proteins to form pseudo-circular nucleocapsid structures (van den Hurk et al, 1977;Mohamed, 1981;de Haan et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The genome consists of three linear ssRNA molecules approximately 3100 (S RNA), 5400 (M RNA) and 8200 (L RNA) nucleotides long, each complexed with N proteins to form circular nucleocapsids (van den Hurk et al, 1977;Mohamed, 1981;de Haan et al, 1989a). Based on this and other properties it has been suggested that TSWV should be considered as a member of the arthropod-borne Bunyaviridae (Milne & Francki, 1984;de Haan et al, 1989 a).…”
Section: Introductionmentioning
confidence: 99%
“…The internal pseudo-circular nucleocapsids consist of three species of ssRNA, denoted S RNA (2916 nucleotides), M RNA (approximately 5000 nucleotides) or L RNA (approximately 8000 nucleotides), which are tightly encapsidated with the nucleocapsid (N) protein (Mr 28.8K) (de Haan et al, 1989 b). In addition a few copies of a large (L) protein (approximately 200K) are present in the virus particle, and may represent the viral polymerase (Mohamed et al, 1973;Mohamed, 1981;Tas et al, 1977).…”
Section: Introductionmentioning
confidence: 99%